Global construction materials database and stock analysis of residential buildings between 1970-2050. (20th February 2020) - Marinova, Sylvia; Deetman, Sebastiaan; van der Voet, Ester; Daioglou, Vassilis
Abstract: Huge material stocks are embedded in the residential built environment. These materials have the potential to be a source of secondary materials, an important consideration for the transition towards a circular economy. Consistent information about such stocks, especially at the global level, is missing. This article attempts to fill part of that gap by compiling a material intensities database for different types of buildings and applying that data in the context of a scenario analysis, linked to the SSP scenarios as implemented in the global climate model IMAGE. The database is created on a global scale, dividing the world into 26 regions in compliance with IMAGE. The potential use of the database was tested and served as input for modelling the housing and material stock of residential buildings for the period 1970–2050, according to specifications made for the SSP2 scenario. Six construction materials in four different dwelling types in urban and rural areas are included. The material flows related to those stocks are estimated and analysed in a companion paper (also exploring commercial buildings) by Deetman et al. (2019). The results suggest a significant increase in the material stock in housing towards 2050, particularly in urban areas. The results reflect specific patterns in the material contents across the different building types. China presently dominates developments in the global level building stock. The SSP2 projections show a stock saturation towards 2050 for China. In other regions, such as India and South East Asia, stock growth is presently just taking off and can be expected to become dominant for global developments after 2050. The database is created to be used as input for resource and climate policymaking as well as assessment of environmental impact related to residential buildings and assessment of possibilities for urban mining. In the future, we hope to extend it as new data on materials in the built environment become available.